STUDENT VIEWS ON THE POPULARITY/PRESTIGE OF TEACHING JOBS: (A case of Georgia, Azerbaijan, Iraq, and the USA/Canada) - Doghonadze, Natela; C. De Bello, Thomas; Aliyev, Aydin; Halawachi, Huda; Ulker, Venera (PROFESSIONAL STUDIES: Theory And Practice, 2023)
According to existing studies, the popularity of teaching jobs is decreasing. Considering the significance of teaching, without which other professions cannot develop efficiently, it is important to assess how acute the problem is and to try to offer some solutions to it. Another goal of the study was to try to develop recommendations on how to raise teaching jobs’ reputation and thus contribute to the improvement of the situation. The goal of the given study, which is a part of three surveys, was to find out students’ views on the prestige of teaching jobs. The main question was ‘Is teaching prestigious?’ An online survey applying a self-made questionnaire was held in Georgia, Azerbaijan, Iraq, and USA with 657 respondents (122 + 362 + 102 +71, consequently). The conclusion was made that the respondents’ attitude towards teachers in these countries is reasonably positive, however, not many of them are planning to become teachers. It was recommended that to increase the prestige of teaching jobs it is necessary, first of all, to raise the quality of teaching, as well as to stimulate book and movie authors and mass media to present the profession to the public more often and positively.